Effect of the supplementation with a ruminal protein activator on weight gain of steers fed rice straw - D’Ascanio, G. N.; Elías, A.; Flores, Angela J.; Rodríguez, R.; Herrera, F. (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the animal response to supplementation with a ruminal protein activator to steers consuming rice straw rolls, an amount of 27 animals of 160 kg were used, distributed into three treatments (rice straw, rice straw + 200g of ruminal protein activator and rice straw + 400 g of ruminal protein activator. animal.d-1). A random blocks design was applied, with three animals per treatment and three repetitions. Mean composition was 4.9 and 45.2 % of crude protein and 61.5 and 20.3 % of neutral detergent fiber for rice straw rolls and the ruminal protein activator, respectively. The control animals, fed only rice straw rolls, lost weight (-0.09 kg.animal.d-1). Treated groups gained 0.242 and 0.325 kg.animal.d-1 (P <0.001) for low and high doses, respectively, although without differences among them. The intake of rice straw rolls increased in 16 % in the treatments supplemented with the activator (P < 0.01), but not between doses. Final efficiency of the use of the activator was 1 g of ruminal protein activator per 1 g of daily weight gain. It is recommended the doses of 1.16 g of ruminal protein activator per kilogram of liveweight. Key words: protein supplementation, low quality forages, protein activator